Biostimulants effectiveness on initial plant growth of common bean (Phaseolus vulgaris L.) - Cargua Chávez, Jessica Elizabeth (2019)
This research aimed to evaluate the effectiveness of biostimulants on the initial growth of bean seedlings (Phaseolus vulgaris L.). The tested biostimulants were amino acids, carbohydrates, Chlorella extract, Ascophyllum nodosum extract, humic and fulvic acids, phytohormones, and a control treatment. The treatment application was carried out by soaking the seeds in biostimulant solutions for 12 hours, then planted in pots of 500gr of capacity, and at seedling emergence the biostimulants were applied through drench. A randomized complete block design with seven treatments, three replicates, and 21 experimental units was carried out. The main variables recorded were root length, leaf area, dry weight, efficacy and relative growth rate (RGR), net assimilation (NA) and leaf area ratio (LAR) at 7, 14, and 21 days after emergence (DAE). Data were subjected to analysis of variance and comparison among means with Tukey at 5% error-probability. Results showed significant differences (p<0.05) for root length, leaf area, and dry weight of seedlings at 21 DAE, where biostimulants based on phytohormones, amino acids, and Chlorella extract showed the best averages when compared with the control; In addition, these treatments showed higher RGR, NA, LAR at 21 DAE. The highest efficacy for dry weight was 143% when applying phytohormones compared with the control. It is concluded that biostimulants were effective on promoting initial growth of bean seedlings.